Gammarus (Amphipoda) species competitive exclusion or coexistence as a result of climate change in the Arctic? - Węsławski, Jan Marcin; Legeżyńska, Joanna; Kotwicki, Lech; Mazurkiewicz, Mikołaj; Olenin, Sergej (Polish Polar Research, 2021)
The coexistence of two congeneric amphipods, boreal Gammarus oceanicus, and arctic G. setosus, was studied during the summer seasons of 2017–2019 in the region of Isfjorden, Forlandsundet, and Prins Karl Forland island in the west-central part of the Svalbard archipelago (Arctic). Across the study area species distribution often overlapped, but the domination patterns mirrored environmental conditions preferred by each species. Both species, however, were able to survive in suboptimal conditions. On a small spatial scale (in one sample) the species were separated, which may suggest an antagonistic relationship between them. The ongoing changes in the environment of Svalbard will likely affect these two species differently. The increasing intrusion of Atlantic waters will probably favor the further expansion of G. oceanicus along the Svalbard coasts. This will be due to the gradual advance of the existing population, as an influx of individuals from the Nordic seas seems unlikely. G. setosus will remain the dominant species in cold-water areas such as the inner fjords and the northeastern coast of Svalbard and may find new suitable habitats in lagoons or estuaries fed by melting glaciers. Despite predicted changes in the distribution range of both species, their future coexistence should still be possible due to the wide range of environmental tolerance and the heterogeneity of the Svalbard coastal habitats.